Y-type hexagonal ferrite high-quality single crystal growth method
Through stage sintering and flux methods, and combined with dilute nitric acid extraction, the problem of the preparation quality and size limitation of hexagonal ferrite single crystals is solved, and high-quality large-size Y-shaped hexagonal ferrite single crystals are obtained, which is promoted. Its application in magnetic memory devices.
Patent Information
- Application Number
- CN202411314265.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-14
AI Technical Summary
In the prior art, the preparation method of hexagonal ferrite single crystals is of poor quality and small size, which limits its development and application in magnetic memory devices.
Stage sintering and flux method are used to eliminate impurities through multiple cycles of rapid temperature-raising and cooling process, combined with dilute nitric acid extraction, and high-quality large-size Y-shaped hexagonal ferrite single crystals are prepared.
The successful acquisition of all Sr high-quality Y-shaped hexagonal ferrite single crystal without Ba provides a material basis for studying its magnetic, ferroelectric properties and potential applications, and overcomes the problems of mass and size limitations in the prior art.
Smart Images

Figure CN119308015A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ferrite ceramic materials, in particular to a method for growing high-quality single crystals of Y-type hexagonal ferrite. Background Art
[0002] Traditional storage devices are mainly magnetic storage devices. The discovery of the giant magnetoresistance effect has further improved the development of traditional magnetic storage devices. Magnetic storage devices have the advantages of easy reading and non-volatile, but they have high energy consumption and large device size. Ferroelectric materials are very insulating. No current is generated during the polarization process of applying an electric field, so the generation of Joule heat is avoided and the energy consumption of the device can be reduced. Therefore, ferroelectric materials can be used as a storage functional material to prepare low-energy magnetic storage. However, ferroelectric materials are easy to write and difficult to read. In multiferroic materials, the electric field can be used to regulate the magnetization state of the sample, and the magnetic field can also be induced. Ferroelectric polarization, not only has the advantages of ferroelectric materials, but also can well overcome the problems of ferroelectric materials. Therefore, considering the high efficiency, energy saving and miniaturization of the device, the emergence of multiferroic materials undoubtedly provides a potential alternative material for this goal.
[0003] Hexagonal ferrite is a typical multiferroic material. Hexagonal ferrite can exist in different forms, including single crystal and polycrystalline forms. Since the polycrystalline samples of hexagonal ferrite are isotropic, their nonlinear magnetoelectric coupling effect at room temperature cannot be effectively studied, which limits their development and application in magnetic storage devices. Single crystal samples have strong anisotropy of magnetic and ferroelectric properties, and have greater application prospects in the field of magnetic storage devices. In order to study the anisotropy of hexagonal ferrite materials and enable the samples to have the greatest potential application value, it is generally necessary to prepare high-quality and large-sized hexagonal ferrite single crystals. However, the preparation methods of hexagonal ferrite single crystals and the prepared single crystal products in the prior art are generally of poor quality and small size. The development of a growth method for high-quality single crystals of Y-type hexagonal ferrite is the focus of research by technicians in this field. Summary of the invention
[0004] The purpose of the present invention is to provide a method for growing high-quality single crystals of Y-type hexagonal ferrite to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is a method for growing high-quality single crystals of Y-type hexagonal ferrite, wherein the chemical expression of the Y-type hexagonal ferrite is Sr 2 Zn 2-x Ni x Fe 12 O22 , x=0-2; the method comprises the following steps:
[0007] Weigh SrCO according to the composition of Y-type hexagonal ferrite 3 , ZnO, NiO and Fe 2 O 3 , mixed with flux, ground to obtain precursor powder; the precursor powder is subjected to staged sintering with changing temperature, and a total of 40 stages of sintering are performed; after the staged sintering is completed, the sintered product is extracted to obtain the Y-type hexagonal ferrite.
[0008] Furthermore, x=0, 1 or 2. That is, the chemical expression of the Y-type hexagonal ferrite is Sr 2 Zn 2 Fe 12 O 22 , Sr 2 ZnNiFe 12 O 22 or Sr 2 Ni 2 Fe 12 O 22 .
[0009] Furthermore, the flux is Na 2 CO 3 .
[0010] The growth method of the present invention is a flux method, using Na 2 CO 3 As flux, the growth is carried out in a single crystal growth furnace. 2 CO 3 As a flux, it can effectively lower the melting point of the precursor powder mixture.
[0011] Furthermore, when x = 0, SrCO 3 , ZnO, Fe 2 O 3 The molar ratio of the flux is 19.69:19.69:53.61:7.01;
[0012] When x = 1, SrCO 3 、ZnO、NiO、Fe 2 O 3 The molar ratio of the flux is 19.69:9.845:9.845:53.61:7.01;
[0013] When x = 2, SrCO 3 、NiO、Fe 2 O 3The molar ratio of titanium dioxide and flux is 19.69:19.69:53.61:7.01.
[0014] Furthermore, the grinding is wet grinding, and the solvent is petroleum ether.
[0015] Furthermore, the grinding time is 3 hours.
[0016] Furthermore, the staged sintering is carried out in a single crystal growth furnace.
[0017] Furthermore, the parameters of the staged sintering are shown in Table 1:
[0018] Table 1
[0019]
[0020] Among them, "room temperature → 300℃" in stage 01 represents heating from room temperature to 300℃ at a constant heating rate, and "100min" represents the time taken is 100min; "300→1420℃", "1420→1100℃" and other meanings in other stages are the same as "room temperature → 300℃" in stage 01, that is, heating or cooling from the temperature on the left side of the arrow to the temperature on the right side of the arrow at a constant heating or cooling rate, and the corresponding time is the time taken in this heating or cooling stage. "300℃" and "120min" in stage 02 represent sintering at 300℃ for 120min; "1420℃", "1800min", "1400℃" and "1080min" in other stages have the same meanings as "300℃" and "120min" in stage 02, that is, sintering at the corresponding temperature for the corresponding time. However, it should be specially noted that the 40-stage "800℃→room temperature" represents the end of the sintering process of the single crystal growth furnace, and the furnace naturally cools to room temperature, so the specific time is not listed.
[0021] The above 40 stages of sintering can be divided into 6 major stages, as follows:
[0022] In the first stage (stage 01-04), the temperature is raised from room temperature to 1420°C and kept at this temperature for 30 h (to allow the solid mixture to completely melt);
[0023] The second stage (05-18 stage) is to quickly raise and lower the temperature from the molten state to the solidified state 1100℃ and keep it at a fixed temperature (mainly to eliminate S-type crystal ZnFe 2 O 4 / NiFe 2 O 4 impurities);
[0024] The third stage (stages 19-36) is to rapidly increase and decrease the temperature between the molten state and the nucleation temperature of 1150°C and to maintain the temperature at a fixed temperature (eliminating the S-type crystal ZnFe 2 O 4 / NiFe 2 O 4 impurities and Y-type ferrite nucleation stage);
[0025] The fourth stage (stage 37-38), the slow cooling crystal growth stage (1150℃-1100℃), the rate is 0.2℃ / h (slow crystal growth stage);
[0026] The fifth stage (39 stages) is a controlled cooling process with a rate of 5°C / min (to avoid rapid cooling at high temperatures that may cause decomposition of the generated crystals);
[0027] The sixth stage (stage 40) is a process of cooling the furnace to room temperature (end of synthesis).
[0028] The advantage of the above staged sintering process is that the sintering temperature is between the high temperature of 1420℃-1240℃ and the low temperature of 1100℃ in the second stage (stage 05-18), and the high temperature of 1240℃-1160℃ and the low temperature of 1150℃ in the third stage (stage 19-36), which is a repeated rapid heating and cooling and long-term heat preservation process. This process eliminates the S-type crystal ZnFe 2 O 4 / NiFe 2 O 4 , and finally synthesized high-quality single-crystal Y-type hexagonal ferrite samples.
[0029] Furthermore, the concentration of the dilute nitric acid is 20wt%; the specific operation of the extraction is: adding 20wt% of dilute nitric acid to the platinum crucible where the sintered product is located, placing the platinum crucible in an ultrasonicator, heating it to 70°C and ultrasonically treating it for 1h, and then soaking it at room temperature for 23h; then pouring the dilute nitric acid into a beaker, washing it with water several times until the poured water is in a clear liquid state.
[0030] Dilute nitric acid can react with sodium carbonate to extract the sample from the solid solvent.
[0031] The second technical solution of the present invention: single crystal Y-type hexagonal ferrite grown by the above-mentioned single crystal growth method.
[0032] The present invention is based on Y-type hexagonal ferrite (Ba, Sr) 2 Me 2 Fe 12 O 22(Me represents a divalent metal ion) and the Sr content is increased to provide a high-quality single crystal product of Y-type hexagonal ferrite without Ba and Sr. The increase of Sr content in the Ba:Sr ratio will lead to more types of magnetic structures, and various properties of Y-type ferrite, such as magnetoelectric coupling and magnetocaloric effect, occur at the transition of magnetic structure. Therefore, increasing the Sr content to induce a variety of magnetic structures is helpful for the subsequent performance research of Y-type hexagonal ferrite.
[0033] In the present invention, Na 2 CO 3 As a flux to reduce the melting temperature, through multiple cycles of rapid heating and cooling process to eliminate S-type ZnFe 2 O 4 / NiFe 2 O 4 Spinel impurities, remove flux Na by dilute nitric acid extraction 2 CO 3 , a pure, high-quality single-crystal Y-type hexagonal ferrite sample containing all Sr is obtained. 2 Technique for the preparation of single crystal samples of scale.
[0034] The present invention discloses the following technical effects:
[0035] The invention successfully synthesizes a high-quality single crystal product of Y-type hexagonal ferrite containing no Ba and containing only Sr.
[0036] The high-quality, large-size Y-type hexagonal ferrite prepared by the method of the present invention provides a material basis for further studying the magnetism, ferroelectric properties, anisotropy of Y-type hexagonal ferrite single crystals, and in-depth exploration of the potential application value of Y-type hexagonal ferrite single crystals. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 The Sr prepared in Example 1 2 Zn 2 Fe 12 O 22 XRD pattern and morphology (the inset is the morphology);
[0039] Figure 2 The Sr prepared in Example 2 2 ZnNiFe 12 O22 XRD pattern and morphology (the inset is the morphology);
[0040] Figure 3 The Sr prepared in Example 3 2 Ni 2 Fe 12 O 22 XRD pattern and morphology (the inset is the morphology). DETAILED DESCRIPTION
[0041] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0042] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0043] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0044] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0045] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0046] The room temperature involved in the specific implementation manner of the present invention is specifically 20-25°C.
[0047] Example 1
[0048] A Y-type Sr 2 Zn 2Fe 12 O 22 (i.e. x=0) A method for growing high quality single crystal of hexagonal ferrite, the steps are as follows:
[0049] Step 1: Preparation of precursor
[0050] (a) Strontium carbonate (SrCO) was weighed in a molar ratio of 19.69:19.69:53.61:7.01. 3 , purity 99.9%), zinc oxide (ZnO, purity 99.99%), ferric oxide (Fe 2 O 3 , purity 99.9%) and sodium carbonate (Na 2 CO 3 , purity 99.999%).
[0051] (b) About 27 g of the above raw materials were placed in a mortar, and petroleum ether (added once every hour, 30 mL each time, a total of 90 mL) was added as a solvent. The mixture was wet-milled for 3 hours to obtain a precursor powder.
[0052] (c) The precursor powder is poured into a platinum crucible and then placed in a single crystal growth furnace.
[0053] Step 2: Preparation of high-quality single crystals
[0054] (a) Staged sintering
[0055] In the single crystal growth furnace, the precursor powder is subjected to staged sintering with changing temperature, and a total of 40 stages of sintering are performed. The parameters of the staged sintering are shown in Table 1:
[0056] Table 1
[0057]
[0058] (b) Extraction: After the staged sintering is completed, pour 20wt% dilute nitric acid into the platinum crucible, place the platinum crucible in an ultrasonicator, heat it to 70°C and ultrasonicate it for 1h (ultrasonic power 600W, frequency 40KHz), then soak it at room temperature for 23h; then pour the dilute nitric acid into a beaker, wash it with water several times and briefly ultrasonicate it (2min) during each washing process to wash away impurities (while using a magnet to absorb the outside of the beaker and the platinum crucible to prevent the sample from falling off), until the poured water is in the form of a clear liquid. Add dilute nitric acid to the platinum crucible again and repeat the above process until the sample is completely extracted from the platinum crucible to obtain Y-type Sr 2 Zn 2 Fe 12 O 22 Hexagonal ferrite single crystal sample.
[0059] Example 2
[0060] A Y-type Sr 2 ZnNiFe 12 O 22 (i.e. x=1) A method for growing high-quality single crystals of hexagonal ferrite, the steps are the same as those in Example 1, except that, during the preparation of the precursor, strontium carbonate (SrCO 3 , purity 99.9%), zinc oxide (ZnO, purity 99.99%), nickel oxide (NiO, purity 99.99%), ferric oxide (Fe 2 O 3 , purity 99.9%), sodium carbonate (Na 2 CO 3 , purity 99.999%).
[0061] Example 3
[0062] A Y-type Sr 2 Ni 2 Fe 12 O 22 (i.e. x=2) A method for growing high-quality single crystals of hexagonal ferrite, the steps are the same as those in Example 1, except that during the preparation of the precursor, strontium carbonate (SrCO) in a molar ratio of 19.69:19.69:53.61:7.01 is used. 3 , purity 99.9%), nickel oxide (NiO, purity 99.99%), ferric oxide (Fe 2 O 3 , purity 99.9%), sodium carbonate (Na 2 CO 3 , purity 99.999%).
[0063] Test Example 1
[0064] The samples prepared in Examples 1-3 were characterized by X-ray diffraction (XRD, model Philips PW1050, Cu Kα ray), with a scanning angle 2θ ranging from 20 to 70° and a scanning speed of 4.8° / min. Figure 1 , 2, 3 as shown, Figure 1-3 The Sr prepared in Example 1 are 2 Zn 2 Fe 12 O 22 , Sr prepared in Example 2 2 ZnNiFe 12 O 22 , Sr prepared in Example 3 2 Ni 2 Fe 12 O2 XRD graph and morphology (the inset is the morphology). After comparing with the standard PDF card, it is found that the c-axis orientation diffraction peak intensity of the sample is obvious, proving that the samples prepared in Examples 1-3 meet the requirements of Y-type ferrite Sr 2 Zn 2-x Ni x Fe 12 O 22 (ICDD No.73-2035). Moreover, the peak intervals are uniform and all are C-axis oriented, which also shows that the obtained samples have a high degree of orientation in structure and are high-quality Y-type ferrites. In addition, the substrate in the morphology image is a standard card, and the size of each small square is 1mm×1mm. It can be seen from the morphology image that the sizes of the samples are 2mm×2mm (x=0), 2mm×2mm (x=1), and 1mm×1mm (x=2).
[0065] The embodiments described above are only descriptions of the preferred embodiments of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for growing high-quality single crystals of Y-type hexagonal ferrite, characterized in that: The chemical expression of the Y-type hexagonal ferrite is Sr2Zn 2-x Ni x Fe 12 O 22 , x=0-2; the method comprises the following steps: SrCO3, ZnO, NiO and Fe2O3 are weighed according to the composition of Y-type hexagonal ferrite, mixed with flux, and ground to obtain precursor powder; the precursor powder is subjected to staged sintering with changing temperature, and a total of 40 stages of sintering are performed; after the staged sintering is completed, the sintered product is extracted to obtain the Y-type hexagonal ferrite.
2. The method for growing high-quality single crystal of Y-type hexagonal ferrite according to claim 1, characterized in that: x=0, 1 or 2.
3. The method for growing high-quality single crystal of Y-type hexagonal ferrite according to claim 2, characterized in that: The flux is Na2CO3.
4. The method for growing high-quality single crystal of Y-type hexagonal ferrite according to claim 3, characterized in that: When x = 0, the molar ratio of SrCO3, ZnO, Fe2O3 and flux is 19.69:19.69:53.61:7.01; When x = 1, the molar ratio of SrCO3, ZnO, NiO, Fe2O3 and flux is 19.69:9.845:9.845:53.61:7.01; When x=2, the molar ratio of SrCO3, NiO, Fe2O3 and flux is 19.69:19.69:53.61:7.
01.
5. The method for growing high-quality single crystal of Y-type hexagonal ferrite according to claim 1, characterized in that: The grinding is wet grinding, and the solvent is petroleum ether.
6. The method for growing high-quality Y-shaped hexagonal ferrite single crystals according to claim 5, characterized in that: The grinding time is 3h.
7. The method for growing high-quality Y-shaped hexagonal ferrite single crystals according to claim 1, characterized in that: The parameters of the staged sintering are shown in Table 1: Table 1 8. The method for growing high-quality Y-shaped hexagonal ferrite single crystals according to claim 1, characterized in that: The extraction is performed by using dilute nitric acid under ultrasonic conditions.
9. Single crystal Y-type hexagonal ferrite grown by the single crystal growth method according to claim 1.
Citation Information
Cited By
Y-type hexagonal ferrite material with dual-element magnetocaloric effect as well as preparation method and application of Y-type hexagonal ferrite material
CN118878314A
Y-type hexaferrite material with dual magnetic heat effect and preparation method and application thereof
CN118878314B